Informations-Bulletin. Kommunistische Partei der Tschechoslowakei. Zentral- Komitee. Internationale Abteilung
Engl.ed.: Information bulletin. Communist party of Czechoslovakia. Central committe International department (ZK 30578) - Russian ed.: Informacionnyj bjulleten. Kommunisticeskaja partija čhechoslovakü. Central'nyj komitet. Mezdunarodnyj otdel (ZK 30308).